Confirmation bias and its relationship to the self confidence I have basic education faculty professors (Journal of the College of Basic Education, 2020)
Learn about the College of education professors affirmative bias.2- Identify the differences in the affirmative bias as a variable type (male-female) learn self confidence among professors of the Faculty of education.3- Identify the differences in self-confidence on as a variable type (male-female) learn the relationship between affirmative bias and confidence in basic education faculty professors. 4- Current research society is determined by the basic education college professors and both sexes Mustansiriyah University and academic year (2018-2019 m) total sample (200) textbook and teaching researcher has adopted affirmative bias scale scale building self confidence and extract their properties The statistical results showed:-. The basic education college professors have the confirmative siding there are differences between males and females in favour of confirmation bias males. The basic education college professors with aplomb. ...sic Educatio